2013
DOI: 10.1016/j.ymben.2013.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Engineered production of fungal anticancer cyclooligomer depsipeptides in Saccharomyces cerevisiae

Abstract: Engineered production of fungal anticancer cyclooligomer depsipeptides in Saccharomyces cerevisiae, Metabolic Engineering, http://dx. doi.org/10. 1016/j.ymben.2013.04.001 This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting galley proof before it is published in its final citable form. Please note that during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(46 citation statements)
references
References 32 publications
0
46
0
Order By: Relevance
“…To identify the respective key enzyme for BEA biosynthesis in the genome of F. fujikuroi , we performed a clustal W alignment with all 18 A‐domains of F. fujikuroi NRPSs, the α‐aminoadipate reductase (AAR) and the A‐domains of the known BEA‐NRPSs from Beauveria bassiana , Fusarium proliferatum , Fusarium oxysporum and Fusarium venenatum (Xu et al ., ; Hansen et al ., ; Zhang et al ., ; López‐Berges et al ., ; Yu et al ., ). This analysis revealed the clustering of NRPS22 (FFUJ_09296) of F. fujikuroi in a clade together with the other BEA‐NRPS‐encoding A domains (Fig.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…To identify the respective key enzyme for BEA biosynthesis in the genome of F. fujikuroi , we performed a clustal W alignment with all 18 A‐domains of F. fujikuroi NRPSs, the α‐aminoadipate reductase (AAR) and the A‐domains of the known BEA‐NRPSs from Beauveria bassiana , Fusarium proliferatum , Fusarium oxysporum and Fusarium venenatum (Xu et al ., ; Hansen et al ., ; Zhang et al ., ; López‐Berges et al ., ; Yu et al ., ). This analysis revealed the clustering of NRPS22 (FFUJ_09296) of F. fujikuroi in a clade together with the other BEA‐NRPS‐encoding A domains (Fig.…”
Section: Resultsmentioning
confidence: 97%
“…Comparison between the SM profile of the WT and the Δ HDA1 mutant by using HPLC‐DAD and HPLC‐HRMS analyses revealed a signal for the cyclooligomer depsipeptide beauvericin (BEA) which was hardly detectable in the WT. BEA is a mycotoxin with carcinogenic properties (Taevernier et al ., ), which is well known from the insect pathogen Beauveria bassiana (Hamill et al ., ; Xu et al ., ), but was also detected in Fusarium proliferatum (Moretti et al ., ; Zhang et al ., ), Fusarium oxysporum (Moretti et al ., ) and Fusarium venenatum (Yu et al ., ). We identified the respective NRPS‐encoding gene for BEA biosynthesis ( BEA1 ) and three additional cluster genes encoding a ketoisovalerate reductase ( BEA2 ), an ABC transporter ( BEA3 ) and a Zn(II) 2 Cys 6 TF ( BEA4 ).…”
Section: Introductionmentioning
confidence: 97%
“…4) in relatively low titers. These results indicated that the N-terminal linker of M23 of BbBEAS 5 and BbBSLS is required for the collaborative work of heterologous M1 and M23. It has been previously reported that short communication-mediating (COM) domains play decisive role in protein-protein recognition in bacterial modular NRPSs such as those in tyrocidine biosynthesis.…”
Section: Figmentioning
confidence: 88%
“…The primary function of BbBEASM1 and BbBSLSM1 is 55 supposed to activate and load D-Hiv onto the CODSs, although we have recently found that BbBEASM1 can also utilize D-Hmv to synthesize beauvericins A-C. 5 We hypothesize that the M1 from BbBEAS and BbBSLS can be exchanged because of the similar function. To test this hypothesis, we made eight co-60 transformations using the eight expression plasmids constructed above.…”
Section: Figmentioning
confidence: 92%
“…14) using Phusion High-Fidelity DNA Polymerase (New England Biolabs) with specific primers (Supplementary Table 2). These PCR products were ligated into the cloning vector pJET1.2 to yield 16 plasmids including pDY83, pDY85, pDY92, pDY93, pDY104, pDY105, pDY106, pDY108, pDY109, pDY111, pDY112, pDY113, pDY135, pDY136, pDY137 and pDY138.…”
Section: Methodsmentioning
confidence: 99%